“Evaluación del Clima Laboral y su Incidencia en el Desempeño Laboral del Recurso Humano en la Empresa Telconet Latam Sucursal Loja" - Orellana Acaro, Ángel Ariel (2024)
The main objective of this research work is to evaluate the work environment and its impact on the performance of human talent in the company Telconet Latam Loja Branch. To do this, the main indicators of the work environment were analyzed, the level of employees' work performance was determined and the relationship between both factors was explored. The research was carried out under a quantitative-qualitative approach, using a census design by applying surveys to all employees of the company. Different dimensions were used such as working conditions, interpersonal relationships, internal communication, organizational structure, professional training, recognition and promotion, motivation and satisfaction, and the psychosocial dimension. The results obtained revealed that there is a significant relationship between the work environment and job performance. Working conditions and internal communication were identified as key factors that positively influence employee performance. Based on these findings, a series of recommendations are proposed aimed at improving the work environment and, consequently, enhancing staff performance.